Efficiency optimization of quantum dot photovoltaic cell by solar thermophotovoltaic system - Talha Hafiz Muhammad; Rana Ahsan Sarwar; Shahid Saleem; Khan Waseem; Naeem Taimoor; Aslam Muhammad; Bahajjaj Aboud Ahmed Awadh; Asghar Aamer Bilal; Conka Zsolt; Stefko Robert (Nanotechnology Reviews)
Obtaining electrical power from solar energy through photovoltaic (PV) cell is an excellent alternative to harvesting energy from fossil fuels. However, efficiency is one of the main concerns as the Shockley–Queisser limit puts an upper bound to the efficiency of PV cell. Solar Thermophotovoltaic (STPV) systems are a viable solution to overcome this limit, but they require efficient and meticulous designs of broadband solar absorber and spectrally selective emitter. These designs require high-temperature tolerance, polarization angle and incidence angle insensitivity, and oxidation resistance to endure high-temperature and harsh environmental conditions. This work presents a Titanium carbide-based ultra-broadband absorber and Platinum-based thermal emitter, both of which are reasonable candidates for STPV applications owing to their high melting points. The proposed absorber has a pyramid design as a top nanostructure layer, while the emitter has gratings on its top. The emitter is optimized for lead sulfide (PbS)-based colloidal quantum dot (CQD) PV cell, having a bandgap energy of 0.41 eV, which is an emerging PV cell technology. The proposed absorber exhibits high efficiency of 96%, while the selective emitter achieves PV cell efficiency of 35.2% for PbS based CQD PV cell at the temperature of 1,350 K.